Review of policies and frameworks on climate change, agriculture, food and nutrition security in Tanzania - Amwata, Dorothy; Tumbo, Madaka; Mungai, Catherine; Radeny, Maren A.O.; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The Republic of Tanzania is an agriculture-based economy. Agriculture contributes 28% of the gross domestic product (GDP), employs 88% of the working population and accounts for between 50% and 66% of exports (TNCCS 2012). Climate change is rapidly emerging as a significant risk affecting agriculture, food and nutrition security in Tanzania. The country is highly vulnerable to recurrent drought, further aggravated by widespread poverty, inequitable land distribution, and low technological capabilities. Climate change is expected to challenge the resilience and adaptive capacities of communities and overwhelm some, by exacerbating existing problems of food and nutrition insecurity.